Network governance in the Philippines - Bautista, Teodoro Lloydon C. (Philippine Journal of Public Administration, 2009)
Alternative delivery systems of public goods and services in the Philippines have grown and contributed in enriching the field of Philippine Public Administration. With the advent and popularity of good governance, participatory governance, community governance, global governance, corporate governance, and indigenous governance, there also arose the term "network governance" which may be considered as the newest fad in an attempt to explain how the distribution of powers, allocation of resources, and processes of decisionmaking has been retransformed. This article tries to establish a conceptual and operational model of network governance in the Philippines. By looking into the experiences of networks, it could map out patterns that uniquely distinguish the type of approaches of network governance in the country. The study underscores the distributive impact of network governance in the political empowerment and presents a working model of network governance that has become an alternative to the traditional modes of governance as gleaned in the successful practice of network governance in the Gawad Kalinga Movement and the PALMA network.